2019
DOI: 10.1186/s12884-019-2390-8
|View full text |Cite
|
Sign up to set email alerts
|

A scalable cognitive behavioural program to promote healthy sleep during pregnancy and postpartum periods: protocol of a randomised controlled trial (the SEED project)

Abstract: Background Poor sleep, including symptoms of insomnia are common during pregnancy and postpartum periods. Poor sleep during the perinatal period is linked to impaired daytime functioning, mood disturbance, and risk for chronic insomnia. Cognitive behavioural therapy (CBT) is consistently shown to be efficacious in treating insomnia, but it is largely inaccessible to new mothers, and surprisingly, not part of current perinatal care. This study aims to evaluate the feasibility and efficacy of a scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The (Bei et al, 2019) for details; (d) work night shift; (e) mental health conditions: major depressive disorder (current); posttraumatic stress disorder (current); panic disorder if associated with nocturnal panic attacks >4 times in the past month; bipolar disorder (lifetime); psychotic disorders (lifetime); substance use disorders (during pregnancy).…”
Section: Methodsmentioning
confidence: 99%
“…The (Bei et al, 2019) for details; (d) work night shift; (e) mental health conditions: major depressive disorder (current); posttraumatic stress disorder (current); panic disorder if associated with nocturnal panic attacks >4 times in the past month; bipolar disorder (lifetime); psychotic disorders (lifetime); substance use disorders (during pregnancy).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that CBT-I helps with adult sleep by increasing sleep drive and altering maladaptive behaviors even when there are environmental factors outside the individual's control. 41 Similarly, mindfulness-based sleep interventions can reduce cognitive arousal and improve insomnia severity. 42 Both therapies may have potential utility for parents experiencing sleep disturbances or higher presleep arousal.…”
Section: Discussionmentioning
confidence: 99%
“…This is a secondary data analysis of a single‐blinded randomized controlled trial comparing behaviourally‐based sleep and diet interventions (Australian New Zealand Clinical Trial Registry: ACTRN12616001462471). The protocol 32 and primary outcome paper 33 have been published elsewhere. The study was approved by the Royal Women’s Hospital (RWH) and the Monash University Human Research Ethics Committees.…”
Section: Methodsmentioning
confidence: 99%